Combined associations of regular exercise and work-related moderate-to-vigorous physical activity with occupational stress responses: a cross-sectional study - Abe, Takafumi; Okuyama, Kenta; Motohiro, Atsushi; Shiratsuchi, Daijo; Isomura, Minoru (Frontiers in Sports and Active Living, 2024)
The association between work-related moderate-to-vigorous physical activity (MVPA) and higher levels of stress response is recognized, but whether this association is moderated by regular exercise remains unclear. This cross-sectional study investigated whether exercise-based physical activity (PA) associates with lower levels of stress responses moderated by work-related MVPA.: The study participants comprised 863 workers from 35 small and medium-sized enterprises in Shimane prefecture, Japan, collected through convenient sampling from April 2021 to August 2022. The Brief Job Stress Questionnaire was used to assess stress responses. Work-related MVPA and exercise-based PA were measured using questionnaires. Multiple linear regression was used to analyze the combined variables of work-related MVPA and exercise-based PA. The reference group had no weekly exercise-based PA and > 60 min of work-related MVPA.Results: When work-related MVPA exceeded 60 min/day, flexibility activity or walking for ≥5 days/week (B=-3.53, 95% ) and muscle-strengthening activity 1-3 times/week (B=-3.52, 95% CI=-6.91, -0.12) were significantly associated with lower psychological stress response. Flexibility activity (B=-1.74, 95% CI=-3.01, -0.46) showed a similar link with physical stress response. When work-related MVPA was below 60 min/day, flexibility activity (B=-3.23, 95% CI=-6.01, -0.44; B=-3.29, 95% CI=-5.94, -0.63) or walking (B=-4.03, 95% CI=-6.62, -1.45; B=-3.10, 95% CI=-5.76, -0.44) practice 1-4 times/week and ≥5 times/week was significantly associated with lower psychological stress response.Exercise-based PA greatly and consistently associates with a lower level of stress responses moderated by work-related MVPA.